2010
DOI: 10.1227/neu.0b013e3181f8d1db
|View full text |Cite
|
Sign up to set email alerts
|

Abciximab Treatment Modalities for Thromboembolic Events Related to Aneurysm Coiling

Abstract: Combined intra-arterial/intravenous administration of abciximab is safe and effective for treating thromboembolic complications that occur during aneurysmal coil embolization with no hemorrhagic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 9 publications
0
35
0
1
Order By: Relevance
“…However, there is no consensus about when and how patients should be loaded with antiplatelet medication before the procedure. Glycoprotein IIb/IIIa antagonists have attracted attention for the prevention or treatment of thromboembolism during coiling of intracranial aneurysms, [5][6][7] but the increased risk of intracranial hemorrhage following glycoprotein IIb/IIIa inhibition remains a substantial concern. Moreover, the safety and efficacy data regarding the use of tirofiban in endovascular aneurysm treatment are lacking.…”
mentioning
confidence: 99%
“…However, there is no consensus about when and how patients should be loaded with antiplatelet medication before the procedure. Glycoprotein IIb/IIIa antagonists have attracted attention for the prevention or treatment of thromboembolism during coiling of intracranial aneurysms, [5][6][7] but the increased risk of intracranial hemorrhage following glycoprotein IIb/IIIa inhibition remains a substantial concern. Moreover, the safety and efficacy data regarding the use of tirofiban in endovascular aneurysm treatment are lacking.…”
mentioning
confidence: 99%
“…Many previous studies that have demonstrated high-infarct rates on postoperative imaging also highlight the fact that many of these infarcts are clinically silent. 1,2,9 We cannot evaluate infarct rates or success of recanalization with thrombolytic agents versus GpIIb/IIIa inhibitors in this study, but better outcomes suggest that GpIIb/IIIa inhibitors are a better option for rescue therapy. 15,16 …”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] The infarction rate among patients receiving rescue therapy ranges between 10% and 40% with higher rates generally seen in studies with postoperative MR imaging [1][2][3][4][5][6][7][8][9][10][11][12][13][14] ( Table 5). In a series of 477 patients with 515 intracranial aneurysms, Ries et al 1 reported that 48 patients (10%) had thromboembolic events; 42 of these patients received rescue therapy with GpIIbIIIa inhibitors, and 1 patient received rescue therapy with recombinant tissue plasminogen activator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used combined IA and IV abciximab to treat the developing thrombi in 39 patients of whom 11 had ruptured aneurysms. They observed 56.5% complete recanalization, amelioration in the TIMI score in 73.9% yet no change was observed in 26.1% 9 .…”
Section: Casementioning
confidence: 94%